New Technologies for Innovation in Public Services: A Review of Case Studies - Dennehy, Ana Inés (2020)
This paper analyses case studies of Artificial Intelligence and Big Data Analytics applications for innovation in digital public services. Recently, many governments at all levels are using these technologies to improve service provision to citizens. However, they are not always aware of their potential for disruption and of the emergent ethical questions. In order to have a better insight of their applications and provide a initial point for policy makers, we review several case studies and analyse how these new technologies are being used to meet specific needs.